2011
DOI: 10.1111/j.1464-5491.2011.03311.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of biomarkers for endothelial dysfunction and procoagulant state on 10-year cardiovascular risk in Type 2 diabetes1

Abstract: In our study, soluble E-selectin and factor XIIa were significantly related to 10-year incident macrovascular events in patients with Type 2 diabetes. These preliminary findings call for replication in larger studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 24 publications
0
5
0
1
Order By: Relevance
“…These observations may be explained by common features in the pathophysiologies of CKD and type 2 diabetes. Risk factors for cardiovascular events such as increased levels of procoagulant biomarkers, anemia and endothelial dysfunction have been shown to be associated with both reduced kidney function [ 40 - 42 ] and type 2 diabetes [ 43 - 45 ]. These factors may act synergistically to increase the risk of cardiovascular events compared with CKD or type 2 diabetes alone.…”
Section: Discussionmentioning
confidence: 99%
“…These observations may be explained by common features in the pathophysiologies of CKD and type 2 diabetes. Risk factors for cardiovascular events such as increased levels of procoagulant biomarkers, anemia and endothelial dysfunction have been shown to be associated with both reduced kidney function [ 40 - 42 ] and type 2 diabetes [ 43 - 45 ]. These factors may act synergistically to increase the risk of cardiovascular events compared with CKD or type 2 diabetes alone.…”
Section: Discussionmentioning
confidence: 99%
“…This was not, however, accompanied by a significant change in urinary excretion of albumin. Soluble E-selectin together with a coagulation factor, XIIa, has been associated with ten-year macrovascular events in subjects with T2D [41]. Poor vitamin D status-related endothelial dysfunction in diabetes may be partly mediated by nuclear factor κ-B (NF-κB)-linked inflammation [42] and endothelial progenitor cell depletion [43].…”
Section: Discussionmentioning
confidence: 99%
“…8 However, an adverse association between E-selectin concentration and macrovascular events, including stroke, has recently been reported among type 2 diabetic patients, with a hazard ratio per 1-U increase in log E-selectin of 2.3 over 10 years of follow-up. 25 Furthermore, a case-control study, including 200 stroke patients and 205 community controls, observed a 3.4-fold and 7.9-fold increased likelihood of ischemic stroke among individuals in the third and fourth quartiles of the E-selectin distribution. 26 The concurrent examination of significant biomarkers in a single multivariable model allowed us to obtain a more parsimonious set of biomarkers of potential importance for ischemic stroke risk prediction.…”
Section: Associationsmentioning
confidence: 99%